2015
DOI: 10.1371/journal.pone.0134588
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Distribution of the Microbial Community of Winogradsky Columns

Abstract: Winogradsky columns are model microbial ecosystems prepared by adding pond sediment to a clear cylinder with additional supplements and incubated with light. Environmental gradients develop within the column creating diverse niches that allow enrichment of specific bacteria. The enrichment culture can be used to study soil and sediment microbial community structure and function. In this study we used a 16S rRNA gene survey to characterize the microbial community dynamics during Winogradsky column development t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 57 publications
(58 reference statements)
3
23
0
2
Order By: Relevance
“…To investigate variability in microbial community development, 100 replicate sediment‐water microcosms (Winogradsky columns) were set up identically. Previous data from multiple experiments in our lab and elsewhere has shown that development of mature Winogradsky column microcosm communities requires 3–4 months, with very few changes in community composition and microcosm function occurring after 12 weeks, while redox potential at all levels in the microcosm declines considerably in the first 10 weeks as cellulose is degraded, then subsequently recovers in the upper water layer while remaining low in the sediment (Pagaling et al ., ; Esteban et al ., ; Supporting Information Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate variability in microbial community development, 100 replicate sediment‐water microcosms (Winogradsky columns) were set up identically. Previous data from multiple experiments in our lab and elsewhere has shown that development of mature Winogradsky column microcosm communities requires 3–4 months, with very few changes in community composition and microcosm function occurring after 12 weeks, while redox potential at all levels in the microcosm declines considerably in the first 10 weeks as cellulose is degraded, then subsequently recovers in the upper water layer while remaining low in the sediment (Pagaling et al ., ; Esteban et al ., ; Supporting Information Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Members of the Spirochaetes have been found to associate with Bacteroidetes to enhance cellulose degradation in the rumen (Kudo et al, 1987), and with the Firmicutes species Clostridium thermocellum for cellulose degradation in co-culture (Pohlschroeder et al, 1994) due to their fermentation of the mono-and di-saccharide products of cellulose breakdown. Moreover, Spirochaetes of the genus Treponema were selected in other studies of Winogradsky columns supplemented with cellulose (Esteban et al, 2015). We therefore examined the temporal variation of OTUs mapping to the four phyla Firmicutes, Bacteroidetes, Spirochaetes and Fibrobacteres during microcosm development.…”
Section: Potential Heterotrophic Degraders Drive Community Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sediments were used as inoculum for Winogradsky-type ( [39]) columns in order to enrich for cyanobacterial biofilms. Winogradsky columns have been used for diversity and enrichment studies, including that of cyanobacteria ( [40]). The enrichments were used for carbonate precipitation experiments in laboratory.…”
Section: Enrichment Using Cyanobacterial Biofilmsmentioning
confidence: 99%
“…The early closed systems were complex and undefined (e.g., using unsterilized pond water) and often poorly replicated, and their initial states and outcomes were difficult to quantify even in terms of species composition (12). In contrast to studies of completely closed systems, microcosm experiments continue to play a major role in microbial ecology and evolution, including classical designs, such as chemostats (13), Winogradsky columns (14), batch bioreactors (15), or long-term serial transfer experiments (16). It is to these designs that we envision adding completely closed systems.…”
mentioning
confidence: 99%